Safety evaluation index on daytime lighting of tunnel entrances - Jiangbi Hu; Xiaojuan Gao; Ronghua Wang; Pengfei Xu; Guangying Miao (Advances in Mechanical Engineering, 2019)
A large luminance difference between outside and inside the entrance of a tunnel, with inappropriate lighting, could result in short-term visual impairment and other hidden dangers. At present, almost all countries use one luminance reduction coefficient index to evaluate the daytime lighting at the tunnel entrance, and their standard values vary. Studies have shown that light sources have three important characteristics: color temperature, color rendering, and luminous intensity, which all play significant roles in driving recognition efficiency. Based on the analysis of driving recognition safety, this article determines the mathematical relationship between recognition distance and luminance reduction coefficient under different color temperatures using experimental data from real vehicles, and studies the difference in recognition demand under different color temperatures. The gray target recognition experiment involved 12 drivers in 36 light environments combined with different color temperatures, luminance levels, and color rendering index of 70 at the tunnel entrance, with good alignment elements and sight distance at the speed of 80 km/h. The results indicate that recognition demands are different under different color temperature conditions and it is more efficient to use both luminance reduction coefficient and color temperature than only luminance index in the appraisal of daytime tunnel entrance lighting.